Target Detection with Distributed Terahertz Sensors. (29th December 2015) - Yu, Yang; Li, Jin; Yang, Xiaobo
Abstract : The distributed target detection system with multiple Terahertz sensors is presented. With the different fusion rules of fusion center, the performance of the system is analyzed. The distribution of THz radar system noise is measured and investigated to confirm the applicability of the detection algorithm in THz band. Experiments with multiple THz sensors are performed to detect single and multiple point-like targets, respectively. The results show that the system proposed is able to detect target while giving the precise coordinates of the target in the observation area.